A Granulocyte-Specific Protein S100A12 as a Potential Prognostic Factor Affecting Aggressiveness of Therapy in Patients with Juvenile Idiopathic Arthritis - Krzysztof Orczyk (Journal of Immunology Research, 2018)
Background. Defining new prognostic biomarkers has become one of the most promising perspectives for the long-term care of patients with juvenile idiopathic arthritis (JIA). The new efficient indicators of disease activity and potential response to treatment are crucial in establishing new therapeutic plans in accordance with the “treat to target” strategy. One of the most studied proteins is called S100A12, which is an alarmin specific for granulocytes, considered as a marker of their activity. Materials and Methods. Study involved 80 patients diagnosed with JIA. Children with systemic subtype were not included in the study. In 53 cases, blood samples were obtained in two time points. Results from the study group were compared to 29 age- and sex-matched healthy individuals. Results. Serum S100A12 levels were higher in JIA than in healthy controls at the study baseline (11.67 ± 6.59 vs. 6.01 ± 2.33 ng/ml). There were no significant differences in S100A12 values between assessed subtypes of JIA. The highest concentrations were observed in patients within a disease flare. S100A12 levels were not dependent from using glucocorticosteroids. The studied protein appeared to be an efficient biomarker for JIA patients: 100% specificity as a diagnostic marker (cut-off level: 10.73 ng/ml) and 100% sensitivity as an indicator of exacerbations within a 3-month observation (cut-off level: 5.48 ng/ml). Conclusions. S100A12 may become an important factor influencing decisions on aggressiveness of JIA therapy. Further elaboration on the clinical algorithm is necessary for that protein to be included in everyday practice.